Mapping species diversification metrics in macroecology: Prospects and challenges - Velasco, Julián A.; Pinto-Ledezma, Jesús N. (Frontiers in Ecology and Evolution, 2022)
The intersection of macroecology and macroevolution is one of today's most active research in biology. In the last decade, we have witnessed a steady increment of macroecological studies that use metrics attempting to capture macroevolutionary processes to explain present-day biodiversity patterns. Evolutionary explanations of current species richness gradients are fundamental for understanding how diversity accumulates in a region. Although multiple hypotheses have been proposed to explain the patterns we observe in nature, it is well-known that the present-day diversity patterns result from speciation, extinction, colonization from nearby areas, or a combination of these macroevolutionary processes. Whether these metrics capture macroevolutionary processes across space is unknown. Some tip-rate metrics calculated directly from a phylogenetic tree (e.g., mean root distance -MRD-; mean diversification rate -mDR-) seem to return very similar geographical patterns regardless of how they are estimated (e.g., using branch lengths explicitly or not). Model-based tip-rate metrics —those estimated using macroevolutionary mixtures, e.g., the BAMM approach— seem to provide better net diversification estimates than only speciation rates. We argue that the lack of appropriate estimates of extinction and dispersal rates in phylogenetic trees may strongly limit our inferences about how species richness gradients have emerged at spatial and temporal scales. Here, we present a literature review about this topic and empirical comparisons between select taxa with several of these metrics. We implemented a simple null model approach to evaluate whether mapping of these metrics deviates from a random sampling process. We show that phylogenetic metrics by themselves are relatively poor at capturing speciation, extinction, and dispersal processes across geographical gradients. Furthermore, we provide evidence of how parametric biogeographic methods can improve our inference of past events and, therefore, our conclusions about the evolutionary processes driving biodiversity patterns. We recommend that further studies include several approaches simultaneously (e.g., spatial diversification modeling, parametric biogeographic methods, simulations) to disentangle the relative role of speciation, extinction, and dispersal in the generation and maintenance of species richness gradients at regional and global scales.